A correlação entre função pulmonar e o estado nutricional de crianças de adolescentes com fibrose cística: uma revisão integrativa da literatura - SOUSA, Washington Miranda de (2024)
INTRODUCTION: Cystic fibrosis (CF) is a genetic disease caused by a mutation in the CFTR gene, which codes for the Cystic Fibrosis Transmembrane Conductance Regulatory Protein. As a multisystem disease, CF mainly affects the respiratory tract, causing recurrent chronic respiratory infections and malnutrition. OBJECTIVES:The aim of this study was to review the literature on the correlation between lung function and nutritional status in children and adolescents with CF. METHODS: This is an integrative literature review, carried out using the BVS, PubMed and SCIELO databases, using the DeCS descriptors: "Cystic fibrosis", "Mucoviscidoses", "Nutritional status", "Nutritition assessment", "Nutrition", "Pulmonary function", "Lung function" and "Respiratory function," from 2000 to 2023. RESULTS: A total of 2417 studies were identified, after which 1216 were excluded following the inclusion criteria, then 324 duplicates were excluded and 877 studies remained for abstract and title selection. This left 58 articles to be read in full text. Of these, 19 remained and were checked for their relevance to the research, of which 11 were excluded as they did not meet the objectives of the topic, as they were not part of the age group studied. Therefore, the research included a total of 8 arƟcles. CONCLUSION: We found that BMI and FEV1 are directly related to lung function and nutritional status in children and adolescents. These were the parameters most commonly used in research. In this sense, we can see the importance of a good nutritional status and its influence on the pulmonary function of these patients.